Analysis of Downhole Throttling Technology of Gas Wells - Ren, Yanfei; Han, Bingyue; Luo, Xuemei (International Journal of Electric Power and Energy Studies, 2024)
Downhole throttling technology relies on downhole throttling to achieve the purpose of wellbore throttling and pressure reduction. Compared with surface throttling, downhole throttling can not only use ground temperature heating, effectively prevent the shaft and wellhead from freezing, but also reduce the wellhead pressure and save the cost of surface pipeline. It solves many technical problems in the process of gas well production, and plays a key role in energy saving and safety production of gas well. At present, a set of mature calculation methods have been developed for the production calculation of conventional gas Wells. However, for throttle gas Wells, due to the influence of fluid accumulation, the accuracy of conventional calculation method is low, which leads to a large error in the selection of throttle size. Therefore, it is of great practical significance to study the downhole throttling technology and optimize the parameters of downhole throttling.